A Case of Isolated Light Chain Deposition Disease in the Duodenum - Kim, Hee-Jun; Park, Eunkyung; Lee, Tae Jin; Do, Jae Hyuk; Cha, Young Joo; Lee, Sang Jae (Journal of Korean medical science, 2012)
Light chain deposition disease (LCDD) is a rare disorder associated with a clonal proliferation of plasma cells, which synthesize abnormal monoclonal immunoglobulin light chains. LCDD is characterized by systemic deposition of light chains in various organs, with the kidneys being most commonly affected. There have been few reports of isolated LCDD. We report a rare case of LCDD limited to a duodenal polyp. A 63-yr-old man visited our hospital for health screening without symptoms in 2009. On gastrofiberscopy, a duodenal polyp was observed. The biopsy showed diffuse infiltration by atypical plasma cells, which were positive for kappa-type light chains by immunohistochemistry. While the patient refused further management, we could find no evidence of recurrence until 2 yr after the initial diagnosis. It has been reported that isolated LCDD has relatively good prognosis compared to systemic LCDD. However, treatment for this disease has not been established yet.